Non-disclosed men who have sex with men within local MSM HIV-1 genetic transmission networks in Guangyuan, China - Lacuo Zhuoma; Yan Zhang; Tu Yan; Fayang Kang; Xueqin Hou; Jianguo Chen; Min Huang; Yali Zeng; Qiushi Wang; Chang Zhou; Shu Liang; Ling Su (Frontiers Media S.A., 2022)
BackgroundMost men who have sex with men (MSM), especially those with HIV infection, do not disclose their same-sex behaviors in China due to Chinese family values and fear of stigmatization, rejection, or prejudice. However, disclosure of same-sex behaviors to healthcare providers (HCPs) can be beneficial for reducing viral transmission and promoting their physical and mental health. In this study, by combining phylogenetic analysis with traditional epidemiological approaches, we tried to identify the MSM who do not disclose to HCPs in transmission networks and explored the factors related to the non-disclosed behaviors.MethodPhylogenetic analysis was conducted using HIV pol sequences obtained from the drug-resistant surveillance program, which was collected as part of routine clinical care since 2012. Sequences were linked to the demographic data collected in the Chinese HIV/AIDS Comprehensive Response Information Management System (CRIMS). First, male patients in whom genetic sequences were within the molecular transmission clusters involving self-reported MSM were identified as potential MSM (pMSM). Then, a cross-sectional survey was conducted to supplement behavioral information and attitudes toward MSM.ResultsOur sample consisted of 190 pMSM patients. In total, 43.16% of the patients were likely to conceal same-sex behaviors during the first-self-report, and 14.73% of patients might continue to conceal a history of same-sex behaviors even after receiving medical care. The pMSM who concealed their same-sex behaviors were reluctant to accept medical services such as Voluntary Counseling and Testing (VCT) and had a lower likelihood of condom use. In addition, the related factors for non-disclosed behavior were associated with current address, income before diagnosis, and attitudes toward MSM.ConclusionNon-disclosure of same-sex behaviors to HCPs may be a major obstacle for certain medical services for MSM who exhibit risky sexual behaviors. The pMSM from developing areas, with high monthly income, and with neutral or un-supportive attitudes toward MSM may represent non-disclosure of their same-sex behaviors. Thus, policies facilitating MSM to disclose their same-sex behaviors are recommended, such as legislations protecting homosexual rights on employment, education, marriage, and so on.